Alterations of adrenal steroidomic profiles in preterm infants at birth. Issue 2 (26th July 2017) - Travers, Simon; Martinerie, Laetitia; Boileau, Pascal; Lombès, Marc; Pussard, Eric
Abstract : Objective: Preterm infants have relative adrenal and kidney immaturity. Recently, we linked their urine sodium loss to a hypoaldosteronism at variance with an appropriate stimulation of the renin-angiotensin system. To investigate this defective aldosterone secretion, we analyse the biosynthesis pathways of adrenal steroids in neonates according to gestational age (GA). Design: Multicentre study (Premaldo) including 152 neonates classified into three groups: group 1 (very preterm (VPT)): <33  gestational weeks (GW); group 2 (preterm (PT)): 33–36 GW and group 3 (term (T)): ≥GW. Method: Steroidomic profiles of mineralocorticoids, glucocorticoids and adrenal androgens were established from umbilical cord at birth (n=152) and peripheral blood at day 3 (n=70) using a recently developed liquid chromatography mass spectrometry method (LC-MS/MS). The enzymatic activity of each biosynthesis step was estimated by the product-to-substrate ratio. Results: At birth, VPT infants exhibit a global defect in adrenal steroid synthesis pathways leading to lower levels of aldosterone, cortisol and androstenedione than in term infants. This defect was strongly related to GA. On day 3, steroid precursors (progesterone, 11-deoxycorticosterone (DOC), 17-hydroxyprogesterone(17-OH-P) and 11-deoxycortisol (S)) were higher in VPT and negatively correlated with GA. Despite of precursors' accumulation, aldosterone and cortisol were similar in the three groups. At birth and day 3, a low cortisol/11-deoxycortisol ratio was found in preterm infants, suggesting an 11-beta-hydroxylase activity ( CYP11B1 ) deficiency. Conclusions: At birth, VPT infants exhibit a global deficit in mineralocorticoids, glucocorticoids and adrenal androgens that attenuates on day 3 of life. Steroid profiling using LC-MS/MS provides evidence for a partial defect in 11-hydroxylase along with prematurity.